La puissance de l'intelligible : La théorie plotinienne des Formes au miroir de l'héritage médioplatonicien - Michalewski, Alexandra (Ancient and medieval philosophy., 2015)
The nature of intelligible Forms received different interpretations from various ancient Platonists. This book sketches the history of these interpretations from Antiochus to Plotinus and shows the radical transformation this theory underwent in the hands of the latter. Pre-Plotinian Platonists considered the Forms as "thoughts of god" and made the causal role of the Forms depend on the craftsman-god. Plotinus rejected this "artificialist" model. Instead he considered the Forms as living and intellective realities and thereby turned the paradigmatic causality of the intelligible on its head. The Forms are themselves active and the demiurge is no longer needed as a causal agent separate from the Forms. Plotinus incorporated key concepts of Aristotelian theology and included them in a doctrine of the causality of the Forms, thus overcoming Aristotle's objections against Platonic Forms.